A mixed methods evaluation of a peer mentoring programme (PASS) for international postgraduate students; Mentee and Mentor perspectives - Menna Brown; Nicole Chartier (Journal of Learning Development in Higher Education)
Peer mentoring provides academic, social, and pastoral support to students. This enhances their educational experience and supports learning. However less is known about the value for international master’s students studying in the UK. To address this gap, this study introduced and evaluated a peer assisted study session (PASS) model of peer mentoring. Mentee expectations were explored at baseline: these were high and varied considerably. The post intervention survey showed students were (78-82%) highly satisfied with the quality, range of topics, usefulness, and opportunities for peer interaction provided by the ten-week, in-person programme. Equally mentors valued the experience; they developed leadership and communication skills, deepened their subject knowledge, and gained transferable skills. Despite this, mentees and mentors alike called for additional, longer sessions, and smaller mentor to mentee ratios to meet the demands and challenges faced by international students. Recommendations and practical implications for programme teams are identified.